P2P file sharing app for android devices sporting IEEE 802.15.4 zigbee radios - Abd Rahman, Akmal Nurhananie; Habaebi, Mohamed Hadi; Ismail, Mahamod (Asian Research Publishing Network (ARPN), 2015)
The peer-to-peer (P2P) file sharing protocol has evolved from depending on Internet connection provided by the cellular network, to free Internet connectivity through Wi-Fi technology. On the other hand, IEEE 802.15.4 is considered as today’s one of the top growing wireless protocol. This paper introduces ZigBee technology, which falls under this standard, into the mobile P2P environment, where it involves devices with Android 4.0 (Ice Cream Sandwich), which is the lowest version of the Android platform that can be found among mobile devices. This paper integrates ZigBee into Android P2P environment and preliminary results showed that it is possible to send and receive files over ZigBee radio, yet the time taken for complete file transfer depends on the file size. Keywords: peer-to-peer, zigbee, android, message broadcasting, file sharing.